Analisis Pengelolaan Retribusi Persetujuan Bangunan Gedung (Pbg) , melalui Sistem Informasi Manajemen Bangunan Gedung (Simbg) dan Keterpaduannya dengan Tata Ruang di Kota Bandar Lampung - Ilmah Nahlani; Muhammad Irfan Affandi; Dedy Yuliawan; Teguh Endaryanto; Bambang Utoyo S (Institut Nalanda, 2026)
Building permit administration plays an important role in controlling spatial utilization and generating local revenue through Building Approval (PBG) retribution. To improve efficiency, transparency, and accountability in permit services, the Indonesian government introduced the Building Management Information System (SIMBG). However, its implementation has not yet been fully optimal in several regions and has not significantly increased local revenue or compliance with spatial planning regulations. This study aims to analyze the implementation of SIMBG in Bandar Lampung City, examine the influence of user characteristics on system utilization, compare PBG retribution revenue before and after SIMBG implementation, and formulate development strategies to strengthen spatial control. A mixed-method approach was employed using quantitative and qualitative descriptive analyses, including text analysis with Orange software, the Mann–Whitney test, and SWOT–QSPM strategic analysis. The results show that SIMBG has improved transparency and accessibility in licensing services. Nevertheless, challenges remain, including limited public understanding, insufficient socialization, and technical constraints. These issues affect the number of PBG applications and regional retribution revenue. Priority development strategies include strengthening institutional capacity, expanding public outreach, improving system features, and integrating SIMBG with spatial planning policies to enhance retribution management and spatial control effectiveness.